Fundamentals of Modern Electric Circuit Analysis and Filter Synthesis A Transfer Function Approach - Izadian, Afshin (Springer International Publishing : Imprint: Springer, 2019)
This textbook explains the fundamentals of electric circuits and uses the transfer function as a tool to analyze circuits, systems, and filters. The author avoids the Fourier transform and three phase circuits, since these topics are often not taught in circuits courses. General transfer functions for low pass, high pass, band pass and band reject filters are demonstrated, with first order and higher order filters explained in plain language. The author's presentation is designed to be accessible to a broad audience, with the concepts of circuit analysis explained in basic language, reinforced by numerous, solved examples. Uses a transfer function approach to circuit analysis, providing useful, pedagogical tips and notes; Expands on modern concepts, in order to use newly introduced topics for realistic applications; Includes numerous, solved and fully explained examples, as well as exercises at the end of each chapter.